Analysis of relief on the map in primary education - Nicoleta-Ioana BOGDAN (Romanian Review of Geographical Education)
The aim of the study is to investigate the effects of using a worksheet to analyze the relief of a small territory, represented on a thematic map. The study involved 16 fourth-grade students. The activity consisted of three stages: in the first stage, a pre-test was applied; in the second stage, students individually analyzed the relief on a hypsometric map and solved the tasks in a worksheet based on this map; in the third stage, a post-test was applied. The results show that students, after the formative intervention, have a greater volume of knowledge about the relief of the commune in which they live. Analyzing the relief represented on the hypsometric map and solving the tasks in the worksheet by students determined positive effects on the volume of knowledge about the relief.